ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH MENABUNG DI BANK JATENG SYARIAH - Akhmad Darmawan; Ninik Dewi Indahsari; Sri Rejeki; Muhammad Rizqie Aris; Roqi Yasin (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
ABSTRACT This study aims to determine the factors that influence customers' interest in saving at Jateng Syariah Bank. This study uses quantitative research methods, non-probability sampling techniques can be obtained through purposive sampling. The population in this study was a customer at Purwokerto Syariah Bank Jateng and was 17 years old. Samples in this study were 170 respondents. The research method used in this study is validity test, reliability test, classic assumption test, multiple regression analysis, coefficient of determination, F test, t test. Location has no significant negative effect on saving interest, Service has a significant positive effect on saving interest, Knowledge has a significant positive effect on saving interest, Promotion has no significant positive effect on saving interest, Product has no significant positive effect on saving interest, Price has no significant positive effect on interest save. Keywords: Location, Service, Knowledge, Promotion, Product, Price, Interest in saving